(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to know (the effect of employing semantic activities on reading comprehension for second grade students in the Arabic language). The researcher followed the experimental approach, and adopted the experimental design with control, partial, which is the design of the control group with the post-test, then the researcher intentionally chose (Osama bin Zaid School affiliated to the General Directorate of Education, the third Rusafa, and the researcher chose the method of random drawing, divisions (b) and (d) as a sample For the research, as Division (B) and the number of its students (30) students represented the experimental group that will study the employment of classroom activities, while Division (D) and the number of its students (30) students represented the control group that will be taught in the traditional way. It was applied to the two research groups (the experimental and the control group) at the end of the experiment, consisting of (25) items, and after correcting the answers, the researcher reached the following result: The students of the experimental group who studied reading subjects according to the use of classroom activities outperformed the students of the control group who studied reading subjects according to the usual method in the reading comprehension test. Thus, the null hypothesis is rejected, which states the following: There is no statistically significant difference at the reading comprehension level. Significance (0.05) between the mean scores of the experimental group whose students studied reading and texts according to the use of classroom activities and the control group whose students studied the same material according to the usual method of reading comprehension